Sudden cardiac arrest as a presentation of Brugada syndrome unmasked by thyroid storm. (30th December 2015) - Korte, Anna K M; Derde, Lennie; van Wijk, Jeroen; Tjan, David H
Abstract : An 18-year-old man suffered a sudden cardiac arrest with ventricular fibrillation and was successfully resuscitated. He had neither a medical nor family history of cardiac disease/sudden death, but was known to have Graves' disease, for which he was treated with radioactive iodine. Recently, block-and-replacement therapy had been discontinued to evaluate thyroid functioning. On admission, thyroid hormone levels were markedly elevated, suggesting thyroid storm due to residual Graves' disease. The patient was treated with propylthiouracil, hydrocortisone and Lugol solution. ECG showed repolarisation patterns suggestive of an underlying type 1 Brugada syndrome (BS). These findings were confirmed by an additional ajmaline test. An implantable cardioverter defibrillator was implanted to prevent future arrhythmias. The patient underwent total thyroidectomy 9 months later and recovered completely. To the best of our knowledge, this is the first reported case of a sudden cardiac arrest as a presentation of BS unmasked by thyroid storm.